2005
DOI: 10.1534/genetics.104.032540
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin (5HT), Fluoxetine, Imipramine and Dopamine Target Distinct 5HT Receptor Signaling to Modulate Caenorhabditis elegans Egg-Laying Behavior

Abstract: Drugs that target the serotonergic system are the most commonly prescribed therapeutic agents and are used for treatment of a wide range of behavioral and neurological disorders. However, the mechanism of the drug action remain a conjecture. Here, we dissect the genetic targets of serotonin (5HT), the selective 5HT reuptake inhibitor (SSRI) fluoxetine (Prozac), the tricyclic antidepressant imipramine, and dopamine. Using the well-established serotonergic response in C. elegans egg-laying behavior as a paradigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
161
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(184 citation statements)
references
References 46 publications
22
161
0
1
Order By: Relevance
“…The hypothesis that the Asm/ceramide system plays a role in the effect of antidepressants was confirmed by the abrogation of the previously-described effect of fluoxetine on egg laying 17,18 , which was abrogated in ams-1-deficient C. elegans (Fig. 2e).…”
Section: A-d)supporting
confidence: 62%
“…The hypothesis that the Asm/ceramide system plays a role in the effect of antidepressants was confirmed by the abrogation of the previously-described effect of fluoxetine on egg laying 17,18 , which was abrogated in ams-1-deficient C. elegans (Fig. 2e).…”
Section: A-d)supporting
confidence: 62%
“…In nearly all tested paradigms, fluoxetine and imipramine induce behavioral changes similarly to exogenous 5-HT Nurrish et al 1999), implying that fluoxetine regulates 5-HT inputs to these neural circuits. However, the tryptophan hydroxylase gene tph-1 is required for 5-HT biosynthesis in C. elegans (Sze et al 2000), mod-5 encodes its sole SERT (Ranganathan et al 2001), and yet fluoxetine could stimulate egg laying and inhibit locomotion in mod-5 and tph-1 mutants Choy and Thomas 1999;Ranganathan et al 2001;Dempsey et al 2005). These findings provided a basis for further investigation into genes and synaptic functions regulated by 5-HT and the impact of fluoxetine on 5-HT signaling.…”
mentioning
confidence: 88%
“…Second, a variety of studies with cultured mammalian cells and mouse brain slices showed that SSRIs and tricyclic antidepressant agents (TCAs) have high affinities to many 5-HT receptor subtypes and act as agonists or antagonists depending on particular receptors being tested (Ni and Miledi 1997;Kroeze and Roth 1998;Eisensamer et al 2003). Third, genetic analyses of the nematode Caenorhabditis elegans in our laboratory and others showed that fluoxetine and the TCA imipramine (Tofrani) could influence behavior independent of SERT function Ranganathan et al 2001;Dempsey et al 2005). In this study, we carried out a systematic survey of SSRIs treatment in C. elegans to gain new insights into actions of SSRIs on the 5-HT system and other neurotransmitter systems.…”
mentioning
confidence: 97%
“…Multiple 5-HT receptors are involved in the regulation of egg laying. Vulval muscle appears to express a Ga q -coupled 5-HT receptor (SER-1) that is coupled to the entry of external Ca 21 through EGL-19, an L-type Ca 21 channel (Shyn et al 2003;Dempsey et al 2005). 5-HT switches the muscle from an inactive to an active state capable of contraction 1 (Waggoner et al 1998).…”
Section: S Erotonin (5-ht) Regulates Key Processes In Nem-mentioning
confidence: 99%